Perjanjian Ilahi dan Konsep Ketuhanan sebagai Basis Keimanan dalam Agama Yahudi - Serlly Della Ressa; Rahmawati; Ahmad Jaiz (AL-Ikhtiar : Jurnal Studi Islam, 2026)
This study aims to examine in depth the sacred covenant (Brit) and the concept of God as the primary foundation for the formation of faith in Judaism. In Jewish tradition, faith is not understood solely as a theological recognition of the oneness of God (YHWH), but rather as a spiritual commitment manifested through concrete obedience to divine laws. Faith is thus closely intertwined with the theological, ethical, and practical dimensions of everyday Jewish life. This study uses a qualitative approach with a literature analysis method, sourced from Jewish scriptures, classical and contemporary theological works, and scientific articles relevant to the study of divinity and the sacred covenant in Judaism. The results of the study indicate that the concept of divinity in Judaism affirms absolute monotheism that positions God as a transcendent, sacred reality, and beyond the boundaries of the material world. This view demands that believers live a law-abiding, morally disciplined, and ethically oriented life as a concrete manifestation of faith. Furthermore, the sacred covenant between God and the Israelites serves as a pillar of religious identity that shapes the collective belief patterns of the Jewish people. Brit is not only interpreted spiritually, but also encompasses moral and social responsibilities embodied in the practice of Torah and mitzvot. Thus, faith in Judaism is built through the integral relationship between the idea of ​​divinity, the sacred covenant, and the practice of obedience, which simultaneously underpins the religious and ethical life of the Jewish people.  Abstrak Penelitian ini bertujuan untuk mengkaji secara mendalam perjanjian suci (Brit) dan gagasan tentang Tuhan sebagai fondasi utama pembentukan keyakinan dalam agama Yahudi. Dalam tradisi Yahudi, keyakinan tidak dipahami semata-mata sebagai pengakuan teologis terhadap keesaan Tuhan (YHWH), melainkan sebagai komitmen spiritual yang diwujudkan melalui ketaatan konkret terhadap hukum-hukum ilahi. Keyakinan dengan demikian terjalin erat antara dimensi teologis, etis, dan praksis kehidupan sehari-hari umat Yahudi. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis literatur, yang bersumber dari kitab-kitab suci Yahudi, karya-karya teologi klasik dan kontemporer, serta artikel ilmiah yang relevan dengan kajian ketuhanan dan perjanjian suci dalam Yudaisme. Hasil Penelitian ini menunjukkan bahwa konsep ketuhanan dalam agama Yahudi menegaskan monoteisme absolut yang menempatkan Tuhan sebagai realitas transenden, suci, dan melampaui batas-batas dunia material. Pandangan ini menuntut umat untuk menjalani kehidupan yang taat hukum, berdisiplin moral, dan berorientasi etis sebagai wujud nyata dari keyakinan. Lebih lanjut, perjanjian suci antara Tuhan dan bangsa Israel berfungsi sebagai pilar identitas keagamaan yang membentuk pola keyakinan kolektif masyarakat Yahudi. Brit tidak hanya dimaknai secara spiritual, tetapi juga memuat tanggung jawab moral dan sosial yang diwujudkan dalam pengamalan Torah dan mitzvot. Dengan demikian, keyakinan dalam agama Yahudi dibangun melalui relasi integral antara gagasan ketuhanan, perjanjian suci, dan praktik kepatuhan, yang secara simultan menopang kehidupan religius sekaligus etis umat Yahudi